EVOLUSI METODE PENGAJARAN PENDIDIKAN AGAMA KRISTEN - Yuliana, Dewi; Gulo, Rezeki Putra (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2024)
This study examines the evolution of teaching methods in Christian Religious Education within the digital era, marked by technological advancements. The research focuses on balancing the preservation of Christian faith traditions with the adoption of future technologies. A qualitative methodology with a thematic approach is employed to critically analyze the challenges and opportunities of integrating technology into religious education. Technologies such as online learning and artificial intelligence offer significant potential to enrich Christian religious education, yet they also present ethical and theological challenges. This article identifies innovative strategies that harmonize traditional pedagogical approaches with technological innovations without compromising spiritual depth and theological values. The findings reveal that the application of technology in Christian Religious Education must consider a balance between practical aspects and the essence of faith, ensuring the relevance of learning for the digital generation while maintaining the integrity of Christian teachings. These findings contribute to developing a holistic and transformative educational model in the modern era.